A nurse-administered 3-Minute diagnostic interview for CAM-defined Delirium (3D-CAM Chinese version) in hospitalized elderly patients: A validation study. (October 2020) - Wang, Jiamin; Lu, Sai; Huang, Yongjun; Ji, Meihua; Yang, Fangyu; Zhang, Yanli; Liu, Hongbin; Li, Fenglian; Wu, Weidong; Bi, Jing; Jin, Xiaolei; Wu, Ying
Abstract: Background: Delirium is a common complication in hospitalized elderly patients, yet often remains unrecognized in the clinical care unit. The newly developed 3-Minute Diagnostic Interview for CAM-Defined Delirium (3D-CAM) has high sensitivity and specificity when administered by trained researchers. However, diagnostic characteristics of the 3D-CAM as performed in routine practice are unclear. Objective: To determine the diagnostic characteristics of a Chinese version of the 3D-CAM administered to hospitalized elderly patients by bedside nurses. Design: A prospective cohort study. Setting: A tertiary geriatric hospital in China. Participants: 323 patients and 49 bedside nurses. Methods: This prospective cohort study was conducted at a tertiary geriatric hospital in China. A Chinese version of 3D-CAM was administered by trained bedside nurses and compared against the reference standard performed by experienced neurologists using the Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition criteria. All assessors were blinded to each other's assessment results. Sensitivity and specificity of the 3D-CAM among bedside nurses were analysed by comparing with the reference standard to test the ability of 3D-CAM in detecting delirium. Results: A total of 323 patients were included in the study, of whom 64 were classified as delirium positive by the neurologists. The 3D-CAM had a sensitivity of 92% (95% confidence interval, 82–97%), specificity of 89% (95% confidence interval, 84–92%), respectively. Conclusion: The Chinese version of 3D-CAM demonstrated good performance as a bedside nurse-administered screening tool for delirium detection among hospitalized Chinese geriatric patients. Registration number: ChiCTR-IOR-17, 010, 368